Jogos sérios para reabilitação de movimentos finos utilizando interfaces naturais - Foletto, Antônio Augusto (2017)
Parkinson’s disease is one of the most common neurodegenerative disorders and its mains symptoms are tremors, movement stiffness and postural instability. The ways to treat the disease are, basically, administration of drugs and physical therapy exercises. The process of rehabilitation through physical therapy is long and could be boring, being hard for patient to keep its routine on therapy programs. Serious games are games that have a purpose that is beyond entertainment like, education, development of skills, or even physical activity. In addition, with the constant evolution of technology, body motion sensors are being introduced in the market and allowing the development of natural interfaces. This way, combining serious games with body motion sensors, like the Leap Motion, was studied as a possible solution to motivation and engagement problems in rehabilitation programs. Three prototypes were developed based on physical therapy’s rehabilitation approaches and using the Leap Motion motion sensor. The prototypes were developed based on a conceptual framework and on guidelines for natural interfaces development that were found on the current literature. The prototypes were played by a control group, formed by healthy individuals, and after each prototype was assessed by the players using the Game Experience Questionnaire. The components main components assessed were immersion, flow, competence, positive affect, negative affect, tension and challenge. As a result, the prototypes presented optimal values related to game experience. High scores were found for positive components like immersion, flow and positive affect and low scores were found for negative components like tension and negative affect. Furthermore, all players reported high levels of hand and fingers usage as well as need for dexterity. This work presented the development of a system of serious games for fine motor skills rehabilitation using natural interfaces that was composed by three serious games that relied on the Leap Motion sensor. All the the prototypes presented good game experience that was statistically equal and that allow therapists to use them with consistency on therapy programs.